A Review of the Participation of Smallholder Farmers in Land-based Carbon Payment Schemes - Tamba, Y.; Wafula, J.; Magaju, C.; St-Jacques, B.; Stiem-Bhatia L.; Arias-Navarro, Cristina; Aynekulu, E.; Winowiecki, Leigh Ann (TMG Research gGmbH, 2021)
There is renewed interest in the engagement of smallholder farmers in carbon markets. This follows in the wake of commitments by governments and companies to reduce or avoid the release of greenhouse gases. It is well known that soil can store large amounts of carbon, and soil stewardship offers a means to harness this potential. However, issues around permanence and scaling in smallholder farmer systems must be addressed if progress is to be made in this area. In this review, we examine the engagement of smallholder farmers in carbon sequestration payment schemes that promote sustainable land management (SLM). Drawing on a review of documents from carbon payment projects, interviews with key informants, and scientific literature, we highlight approaches for smallholder engagement along the project cycle, identify key barriers to participation, and outline options to enhance farmers’ agency. In assessing a total of ten projects, we observe considerable variation in participation across the projects.